Production appraisal of police patrol - Brewer, Robert C. (American journal of criminal justice, 1979)
Due to the increase in public expenditures for police protection during the past decade, it has become increasingly important to accurately measure patrol and service productivity. This article reviews conventional patrol and service practices and offers specific suggestions for improvement of patrol productivity.